2021
DOI: 10.32718/nvlvet10210
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of iron-containing drugs for the prevention of iron deficiency anemia in piglets

Abstract: Prevention of iron deficiency anemia in piglets is an important preventive measure to ensure the health of pigs, as mortality from this pathology is quite high, and animals that recover from treatment do not realize their own potential productivity. The aim of our study was to evaluate the effectiveness of the use of iron (IV) clatrochelate in combination with cyanocobalamin for the prevention of iron deficiency anemia in piglets compared to the traditional scheme of prevention of this disease. To achieve this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
3
7
0
Order By: Relevance
“…During the entire study period, the hematocrit was probably higher in the piglets of the control group, and the highest difference was on days 9 and 12 by 1.85 and 2.19 times, respectively. Such data coincide with previous studies (Derkach, 2021), according to which the hematocrit was probably higher in the control group during the whole period of the study, and the difference was also the highest on days 9 and 12 by 1.7 and 1.9 times, respectively. The findings of the current study indicated that the value of hematocrit in the blood of piglets of the experimental group was within physiological values.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…During the entire study period, the hematocrit was probably higher in the piglets of the control group, and the highest difference was on days 9 and 12 by 1.85 and 2.19 times, respectively. Such data coincide with previous studies (Derkach, 2021), according to which the hematocrit was probably higher in the control group during the whole period of the study, and the difference was also the highest on days 9 and 12 by 1.7 and 1.9 times, respectively. The findings of the current study indicated that the value of hematocrit in the blood of piglets of the experimental group was within physiological values.…”
Section: Resultssupporting
confidence: 92%
“…This tendency of changes in the hemoglobin content of piglets' blood in the experimental group under the influence of iron (IV) clathrochelate and cyanocobalamin differs slightly from the dynamics under the influence of iron (IV) clathrochelate. In previous studies (Derkach, 2021), it was noted that the hemoglobin content in the blood of piglets in the experimental group from days 5 to 30 was probably lower than the control by 1.1-1.3 times, while in other periods it did not differ from the control. However, under different prevention schemes in all periods of the study, the content of hemoglobin in the blood of piglets in the control and experimental groups was within physiological values.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations